Eksperimental Penambahan Lapisan Karung Plastik Dan Abu Sabut Kelapa Terhadap Nilai Kuat Geser Tanah Lempung. - Rismuhad Rahman; Virgo Trisep Haris; Lusi Dwi Putri (JURNAL RIVET, 2025)
Land has a very important role in the world of construction such as buildings, bridges, and also road construction. Soil acts as the foundation of construction where the soil must be able to withstand the construction load that stands on it. On Jalan Badak, Tenayan Raya District, Pekanbaru City, Riau Province will be built housing and rigid roads. The problem is, in other locations that are not far from the construction site, there is also a subsidence (change in volume) in the construction of rigid roads due to the traffic load on it. This study aims to analyze the value of shear strength in clay soil stabilization using layers of plastic sacks and coconut coir ash waste. The research method is an experimental study in the laboratory based on SNI 3420:2016 using clay soil taken from Jalan Badak Ujung, Pekanbaru City, Riau. Soil stabilization material with a mixed variation percentage of 15% of the dry weight of the soil. There are 3 variations used, variation 1 is the top plastic sack layer and the ask 15% mixture, variation 2 is the bottom plastic sack layer and the ask 15% mixture, variation 3 is the top and bottom plastic sack layer and the ask 15% mixture. The test specimen is fermented for 7 days, then the sample is tested using a direct shear tool . The results showed a significant increase in the variation 3 test specimen, where the shear strength of the soil increased by 122.06% and the cohesion value increased by 54.35%.